THE EFFECTIVENESS OF USING JURNAL.ID IN IMPROVING THE EFFICIENCY OF ACCOUNTING PROCESSES IN VILLAGE-OWNED ENTERPRISES (BUMDES) - Pramawati, I Dewa Ayu Agung Tantri Pramawati; I Kadek Budi , Sandika; I Kadek Dwi Gandika, Supartha; Ni Putu Ayu Siska , Wulantari (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
Digitalization has become an urgent need in financial management, including in Village-Owned Enterprises (BUMDes). This study aims to evaluate the effectiveness of Jurnal.id, a cloud-based software, in improving the efficiency of accounting processes in BUMDes. The methodology includes literature review, surveys, interviews, and data analysis. The study also identifies implementation challenges, such as a lack of infrastructure and technological knowledge. Preliminary results show that using Jurnal.id enhances accuracy, transparency, and time efficiency in BUMDes financial management. By providing training, policy support, and improving digital infrastructure, Jurnal.id can serve as a strategic solution for driving BUMDes' digital transformation. Based on survey, interview, and observation results, the majority of users expressed satisfaction with Jurnal.id's interface, rating its design as good or excellent. This indicates that Jurnal.id's interface is intuitive, easy to understand, and improves user experience.